The role of interventional radiology in hepatic and renal hemorrhage embolization: single center experience and literature review - Sgalambro, Ferruccio; Giordano, Aldo Victor; Carducci, Sergio; Varrassi, Marco; Perri, Marco; Arrigoni, Francesco; Palumbo, Pierpaolo; Bruno, Federico; Bardi, Luca; Mangoni di S. Stefano, Maria Luisa; Danti, Ginevra; Gentili, Francesco; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Intraabdominal hemorrhage secondary to liver and kidney injury is a major cause of morbidity and mortality. Endovascular arterial embolization is an established interventional radiology technique used to treat active bleeding, and its role in managing abdominal hemorrhages is growing, given the increasing trend for conservative treatment. Our study aims to retrospectively evaluate the technical and clinical results and the possible complications of arterial embolization procedures performed in emergency, in post-traumatic, iatrogenic, and pathological hepatic and renal bleedings. Methods: We performed a ten-year, single-center retrospective survey (from January 2010 to December 2019) of all patients treated in emergency by intra-arterial embolization of liver and kidney bleeding. Preliminary CT angiography studies were evaluated, as well as the angiographic findings. Materials used, procedural data, and clinical outcomes, including complications, were recorded. Results: The diagnostic angiography showed a single source of bleeding in 20 cases (66.7%), two bleeding vessels in 4 cases (13.3%), and multiple hemorrhagic sources in 6 cases (20%). All bleeding sources were successfully embolized; in 12 patients (40%), complete embolization was achieved with coils and 18 patients (60%) with hemostatic sponges. In one case, a second embolization procedure was performed for the persistence of hemodynamic instability. No major post-procedural complications were recorded. The mean procedure duration was 65.1 minutes. Conclusions: Based on our experience and literature data, the treatment of endovascular embolization in acute abdominal bleeding of hepatic and renal origin represents the treatment of choice, as it can provide complete therapeutic success in hemodynamically stable patients. (www.actabiomedica.it)